Developing LEGAMAT on Geometric Distribution: A Teaching Tools for Understanding Mathematics Concept - Cahyaningsih, Desi; Khairunnisa, Alya; Safitri, Azzahra Indah; Kholifah, Nur; Jumrotin, Resti; Rani, Rondiah Novi; Putri, Ratu Ilma Indra; Sari, Novita; Sukma, Yovika (Jurnal Pendidikan Matematika, 2024)
The traditional approach to teaching geometric distributions, which focuses on proving theorems, makes it difficult for students to apply the concept in everyday life. Moreover, the content delivered by the teacher is challenging for students to understand.  Therefore, developing learning media to increase student interest and understanding of the concept was necessary. In response to these challenges, the researchers developed 'Lempar Gelang Matematika (LEGAMAT)', a set of teaching tools for geometric distributions, accompanied by a student worksheet. Consequently, this study aimed to produce valid and practical teaching tools. This study employed a design research method with two stages: the preliminary stage (preparation and design stage of teaching tools and Student Worksheet) and the formative evaluation stage (evaluation and revision stage). The participants of this research were nine pre-service teachers. The data were collected by walkthrough, observation, and interview. The collected data was analyzed qualitatively. Based on the results of expert judgments and trials at the one-to-one stage, it was found that the set of LEGAMAT teaching tools was valid in media appearance aspects, easiness aspects, aesthetic aspects, and usage requirements aspects. It is practical to be used by students based on the observation in the small group stage. The researchers suggested that further studies continue until the field test stage to determine the effectiveness of the teaching tools. Additionally, they recommended developing other teaching tools related to geometric distribution topics. Proses pembelajaran distribusi geometri, yang biasanya terbatas pada pembuktian teorema, membuat siswa sulit ketika konsep tersebut diterapkan dalam kehidupan sehari-hari. Selain itu, materi yang disampaikan oleh guru sulit untuk dipahami oleh siswa. Oleh karena itu, diperlukan pengembangan media pembelajaran untuk menambah minat belajar serta membantu siswa memahami materi pembelajaran tersebut. Berdasarkan hal tersebut, peneliti mengembangkan media pembelajaran berupa Alat Peraga yaitu Lempar Gelang Matematika (LEGAMAT) dengan Lembar Kerja Peserta Didik. Adapun tujuan dari penelitian ini adalah untuk menghasilkan alat peraga yang valid dan praktis. Metode yang digunakan dalam penelitian ini adalah Design Research tipe Development Study yang terdiri dari dua tahap yaitu tahap pendahuluan (tahap persiapan dan perancangan alat peraga dan Lembar Kerja Peserta Didik) dan tahap evaluasi formatif (tahap evaluasi dan revisi). Adapun subjek dari penelitian ini adalah 9 orang mahasiswa calon guru. Pengumpulan data dilakukan dengan cara walkthrough, observasi, dan wawancara. Data yang terkumpul dianalisis secara kualitatif. Berdasarkan hasil expert judgement dan uji coba tahap one-to-one diperoleh hasil bahwa seperangkat ajar LEGAMAT valid baik isi, konstruk, dan bahasa. Seperangkat alat ini praktis digunakan oleh mahasiswa calon guru berdasarkan observasi pada tahap kelompok kecil. Peneliti menyarankan agar peneliti selanjutnya melanjutkan penelitian hingga tahap field test, sehingga dapat mengetahui keefektifan perangkat pengajaran dalam proses pembelajaran. Peneliti juga menyarankan untuk mengembangkan perangkat pengajaran lain yang berkaitan dengan topik sebaran geometri.